Detectable respiratory SARS‐CoV‐2 RNA is associated with low vitamin D levels and high social deprivation. Issue 7 (24th April 2021) - Livingston, Mark; Plant, Aiden; Dunmore, Simon; Hartland, Andrew; Jones, Stephen; Laing, Ian; Ramachandran, Sudarshan
Abstract: Background: Accumulating evidence links COVID‐19 incidence and outcomes with vitamin D status. We investigated if an interaction existed between vitamin D levels and social deprivation in those with and without COVID‐19 infection. Methods: Upper or lower respiratory tract samples from 104 patients were tested for SARS‐CoV‐2 RNA in accordance with Public Health England criteria (January‐May 2020) using RT‐PCR. The latest serum total 25‐hydroxyvitamin D(25‐OHD) levels, quantified by LC‐MS/MS, was obtained for each patient (September 2019‐April 2020). Index of Multiple Deprivation (IMD) was generated for each patient. Univariate and logistic regression analyses examined associations between age, gender, 25‐OHD, IMD score and SARS‐CoV‐2 result in the total cohort and subgroups. Results: In the total cohort, a positive SARS‐CoV‐2 test was significantly associated with lower 25‐OHD levels and higher IMD. A positive test was associated with higher IMD in the male subgroup and with lower 25‐OHD levels in those aged >72 years. Low 25‐OHD and IMD quintile 5 were separately associated with positive COVID‐19 outcome in the cohort. Patients in IMD quintile 5 with vitamin D levels ≤ 34.4 nmol/L were most likely to have a positive COVID‐19 outcome, even more so if aged >72 years (OR: 19.07, 95%CI: 1.71‐212.25; P = .016). Conclusions: In this cohort, combined low vitamin D levels and higher social deprivation were most associated with COVID‐19 infection. In older age, this combination was even more significant. Our data support the recommendations for normalising vitamin D levels in those with deficient / insufficient levels and in groups at high risk for deficiency.